A meta-analysis of the effects of monensin supplementation on beef cattle performance, digestion and ruminal parameters in three feeding systems - Ribeiro, Richard Vaquero [UNESP] (2025)
This meta-analysis evaluated the effects of monensin supplementation on beef cattle performance, ruminal parameters, and total tract digestibility in different feeding systems, including total mixed ration (TMR), partial TMR (pTMR), and pasture. The dataset included 131 peer-reviewed publications that comprised 349 treatment means. The effects of monensin supplementation were evaluated using the weighted mean differences (WMD) between the control (diets without monensin) and treatment (diets with monensin) groups. Heterogeneity was explored through meta-regression and subgroup analysis, which considered factors inherent to the animal such as diet, monensin dose, and experimental traits. Monensin supplementation reduced (P < 0.01) dry matter intake (DMI) (pasture: −0.92 kg/day; pTMR: −0.12 kg/day, and TMR: −0.25 kg/day) and increased (P < 0.01) average daily gain (ADG, 0.06, 0.05 and 0.02 kg/day, respectively) in all feed systems. In the pTMR system, genetic group and experimental design influenced (P < 0.01) the effect of monensin on ruminal propionate and butyrate concentrations. Additionally, supplement intake and type affected the effect of monensin on feed conversion ratio (FCR) and ruminal propionate concentration. In the pTMR system, a monensin intake of 200–300 mg/day promoted the greatest improvement in FCR (WMD = −1.07 kg/kg; P = 0.011). In the TMR system, genetic group, sex class, fattening period, and dietary concentrate and crude protein levels influenced (P < 0.01) the effect of monensin on DMI and ADG. Forage type affected the effect of monensin on ADG, acetate, butyrate, and isovalerate (P < 0.01). Monensin inclusion of up to 15 mg/kg DM in TMR diets improved FCR (WMD = −0.54 kg/kg; P = 0.001) and increased ADG (WMD = 0.055 kg/day; P = 0.001). Thus, monensin consistently increased ruminal propionate concentration and improved beef cattle performance and feed efficiency, but the extent of these responses varied depending on dietary, animal, and experimental factors in each feeding system.